Facile Synthesis of Functionalized 1, 4‐Benzodiazepine‐3‐One‐5‐Acetates via [4 + 3]‐Annulation of Azaoxyallyl Cations With 2‐Aminophenyl α, β‐Unsaturated Esters. (8th July 2020) - Jang, Hyun Sun; Kwon, Yong Il; Kim, Sung‐Gon
Abstract : A metal‐free [4 + 3]‐annulation of α‐halohydroxamates with 2‐aminophenyl α, β‐unsaturated esters has been developed for the construction of seven‐membered 1, 4‐benzodiazepine‐3‐one‐5‐acetates in moderate to good yields (up to 82% yield). The annulation involved the cascade reaction of an generation of azaoxyallyl cation, aza‐addition to this azaoxyallyl cation, and intramolecular aza‐Michael reaction to yield 1, 4‐benzodiazepine‐3‐one‐5‐acetates. Abstract :